2012
DOI: 10.12806/v11/i2/rf6
|View full text |Cite
|
Sign up to set email alerts
|

The perception and implementation of sustainable Leadership strategies in further education colleges

Abstract: Sustainable leadership as a concept is both in its infancy and also under researched, with much of the previous work in the area concentrating solely on the compulsory sector. Lambert (2011) argues that existing models are not entirely appropriate for further education due to the landscape in which colleges operate. This paper presents the findings of empirical work which sought the views of principals of general further education colleges (equivalent to United States Community Colleges) in the south east of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 24 publications
1
41
0
8
Order By: Relevance
“…Sustainable leadership concept in education were analysed by scientists as Hargreaves, Fink (2004), Hoyle, Wallace (2005), Bottery (Botery et al 2008; Botery 2012), Morrison (2010), Lambert (2012) and others. According to Lambert (2012) sustainable leadership in education sector is its infancy (Lambert 2012). Hargreaves, Fink (2004) developed a model of sustainable leadership in education sector particularly primary, secondary and post-secondary.…”
Section: Theoretical Aspects Of Sustainable Leadership Organisationamentioning
confidence: 99%
“…Sustainable leadership concept in education were analysed by scientists as Hargreaves, Fink (2004), Hoyle, Wallace (2005), Bottery (Botery et al 2008; Botery 2012), Morrison (2010), Lambert (2012) and others. According to Lambert (2012) sustainable leadership in education sector is its infancy (Lambert 2012). Hargreaves, Fink (2004) developed a model of sustainable leadership in education sector particularly primary, secondary and post-secondary.…”
Section: Theoretical Aspects Of Sustainable Leadership Organisationamentioning
confidence: 99%
“…Building on this, Leader (2004) emphasises the value of allowing middle manager to shape vision and strategy, rather than them simply being a used as a tool for its implementation. Due to the potential shortage in educational leaders it is essential to develop middle managers into strategic visionaries (Lambert 2012).…”
Section: Expectations and Challenges Of Further Education Middle Managersmentioning
confidence: 99%
“…The concept of sustainable leadership in education has been analyzed by scholars such as Hargreaves and Fink [24], Hoyle and Wallace [28], Fullan [23], Bottery [20], and Lambert [33,34]. According to Lambert [44], sustainable leadership in the education sector is at its beginning.…”
Section: The Role Of Lifelong Learning For Sustainable Leadership In mentioning
confidence: 99%
“…Lambert, as a result of his study, emphasized that the development of sustainable leadership would be effective in developing the skills needed for individuals in higher-level roles. Similarly, Lambert [34] has established a sustainable leadership framework in the education sector consisting of six factors including human capacity, strategy and partnership building, developing long-term goals from short-term goals, diversified workplace building, and courses. In another study, Šimanskienė and Župerkienė [35] revealed the differences between sustainable leadership and non-sustainable leadership.…”
Section: The Role Of Lifelong Learning For Sustainable Leadership In mentioning
confidence: 99%
See 1 more Smart Citation